Investigation of Electrochemical, Thermal and Electrical Performance of 3D Lithium-Ion Battery Module in a High -Temperature Environment - Sharma, Snigdha; Panwar, Amrish Kumar; Tripathi, Madan Mohan (International Journal of Renewable Energy Development, 2020)
In the present time, the rechargeable lithium-ion battery is being commercialized to meet the sustained market’s demands. To design a more reliable, safe, and efficient Li-ion battery, a 3-D simulation study has been presented in this paper. In this study, a lithium-ion coin-cell is proposed which has LiFePO4 as a positive electrode with a thickness of 1.76 µm, carbon as a negative electrode with a thickness of 2.50 µm and Celgard 2400 polypropylene sheet as a separator between the electrodes with a thickness of 2 µm. The proposed Li-ion battery has been designed, analyzed, and optimized with the help of Multiphysics software. The simulation study has been performed to analyze the electrochemical properties such as cyclic voltammetry (CV) and impedance spectroscopy (EIS). Moreover, the electrical and thermal properties at the microscopic level are investigated and optimized in terms of surface potential distribution, the concentration of electrolyte, open circuit, and surface temperature with respect to time. It has been noticed that the peak voltage, 3.45 V is observed as the temperature distribution on the surface varies from 0 OC to 80 OC at a microscopic scale with different C-rates. The analysis of simulation results indicates a smoother electrode surface with uniform electrical and thermal properties distribution resulting in improved reliability of the battery. The performed simulation and optimization are helpful to achieve control over battery performance and safe usage without any degradation of the environment.